Characterization of antiseptic gel with the addition of eucalyptus and grapefruitessential oils as an active ingredients - Asri Widyasanti; Rizqita Thifal Shalsabilla (Universitas Darussalam Gontor, 2020)
n the era of the COVID-19 virus pandemic, antiseptic products have become very popular. One of them is an antiseptic for hands which is known as hand sanitizer. There are three hand sanitizers available in the market, namely liquid, gel, and foam hand sanitizers. Hand sanitizers are an easy solution for cleaning hands when soap and water are not available. Hand sanitizers are considered practical to use because they do not require water and are suitable for carrying when on outdoor activities. This product is an alternative product for washing hands with soap. However, the continuous use of alcohol and triclosan in the hand sanitizer can erode skin moisture and cause skin irritation. Therefore, it is necessary to utilize natural active ingredients that have the potential to be antibacterial, namely essential oils. The purpose of this study was to determine the effectiveness of eucalyptus and grapefruit essential oils as natural active ingredients in hand sanitizers and to test their quality based on SNI 06-2588-1992. The method used in this research was a laboratory experiment with descriptive analysis. Parameter observed on liquid hand sanitizers were chemical properties (pH), physical properties (specific gravity, liquid emulsi, and organoleptic properties. The analysis showed that the hand sanitizer formulation with the active ingredient of Eucalyptus and Grapefruit essential oils has a pH of 7.5, a specific gravity of 0.9098, and a stable emulsion preparation. Organoleptic results of the level of preference for hand sanitizer products, in terms of color = 4.04 (like-very-like), aroma = 3.92 (normal-like), viscosity = 3.08 (normal-like), impression when using = 3.52 (normal-like), after-use impression (rough impression) = 3.36 (normal-like) and there are found no skin irritation, respectively. The process technology for making handmade hand sanitizers with the addition of eucalyptus and grapefruit essential oils could be developed so that they can be applied on an industrial scale